Peranan Hukum Pajak Sebagai Sumber Keuangan Negara Pada Pembangunan Nasional Dalam Upaya Mewujudkan Kesejahteraan Rakyat - Divya Reyvani; Ika Damai Sari; Putri Yuanita; Dini Vientiany (CV. ITTC INDONESIA, 2024)
The purpose of this research is to find out how the role of tax law as a source of state finance on national development in the effort to realize people’s welfare, Taxation is one of the tools of public policy that cannot be avoided to regulate and maintain the economic stability of the country. This research uses a qualitative method in which research is conducted in the library through the collection of books, documents, archives, and other types. tax law has a very important role as a source of state finance in national development. Through a good and effective taxation system, the state can collect the revenue needed for infrastructure development, public services, and people's welfare programs. Thus, tax law not only functions as an instrument of revenue collection for the state, but also as a tool to achieve national development goals and realize people's welfare. This research shows that tax law does not only serve as an instrument of revenue collection, but also as a tool to achieve national development goals and realize welfare for all the people.